PERAN MEDIATOR DALAM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL DI DINAS TENAGA KERJA KOTA PEKANBARU (STUDY KASUS BENNY HENGKI REKSON SILALAHI DAN PT. ASURANSI JIWA BUMI ASIH JAYA PEKANBARU) - Gaol, Renny Renovawaty Lumban; Lestari, Rika; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Labor relations between workers and employers not always get well. Sometimes one or both parties do not exercise their rights and obligations that have an impact on industrial relations disputes. Industrial disputes can be resolved in two ways: through out of court (non liigasi) and the courts (litigation). The parties to the dispute shall take the out of court settlement through before proceeding to court. Basically the settlement may be conducted by each party through consensus. but often do not find an agreement. So the settlement will be taken through the mediation brokered by a mediator.This type of research is classified in socio-juridical kind of research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted at the Energy Work Office at Pekanbaru, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data and data tertiary, data collection techniques in this study with interviews, and review of the literature.From the research, there are two main issues that can be inferred. First, the role of mediator is a intermediary who uncommitedin mediation session to help the disputing parties to lead the mediation hearing without favoring one of the parties to the dispute, but the industrial dispute between perkeja and PT Asuransi Jiwa Bumi Asih Jaya Pekanbaru brokered by a mediator suggested to workers to accept gifts in the form of wages the company two months. This is quite contrary to the role of a neutral mediator who just attitude given that the mediator itself knows that giving from company notto fit with the rule. Mediator in the trial also must explain to the parties to the dispute about rights and obligations, in the case of an industrial dispute labor is minimal knowledge of the rights and obligations, so that workers become employees PKWT in the company for 9 (nine) years without learned that the company has violated the rule on Employment Agreement Specific time (PKWT). And the mediator should be able to create an atmosphere conducive trial and comfortable so that when the mediation hearing the parties feel comfortable walking along both disputing parties are satisfied with the hearing process mediasi. second, Barriers experienced by the mediator in the settlement of disputes between Benny Hengki industril Rekson Silalahi and PT Asuransi Jiwa Bumi Asih Jaya Pekanbaru is difficulty of bringing together the interests of the different parties, less the proof or information who need mediator, mediator not have the force to vigour.Keywords: Role of Mediator – Industrial Dispute - Mediation